Revision of the type series of the original species placed in the genus Pintalia Stål, 1862 (Hemiptera: Fulgoromorpha: Cixiidae), and description of 12 new species from Brazilian caves - Santos, Júlio César Do Carmo Vaz; Hoch, Hannelore; Bartlett, Charles R.; Ferreira, Rodrigo Lopes (Zootaxa, 2025)
Here we redescribe the nine original species of Pintalia Stål, 1862 (Hemiptera, Fulgoromorpha, Cixiidae) based on type specimens from Brazil and provide an emended diagnosis for the genus. We provide an amended description of P. constellaris (Walker, 1858) with images of the fresh specimen. Furthermore, we describe twelve new species recently found in Brazilian caves in three proposed species-groups: Pintalia pictipennis-group, which includes P. pictipennis Stål, 1862, P. propria Muir, 1934, P. minuta sp. nov., P. minima sp. nov., P. magnaepiprocti sp. nov., P. serratilis sp. nov. and P. stali sp. nov.; Pintalia constellaris-group, which includes P. constellaris (Walker, 1858), P. ecuadorensis Muir, 1934, P. speciosa sp. nov and P. fennahi sp. nov.; and Pintalia painensis-group, which includes P. painensis sp. nov., P. dorensis sp. nov., P. lundi sp. nov., P. montalvaniensis sp. nov., and P. muiri sp. nov. Adults and nymphs of the new species herein described were observed inside caves feeding on roots from epigean vegetation and are hence tentatively classified as subtroglophiles, eutroglophiles and troglobionts. The new species were collected from caves in Minas Gerais state and Bahia state. A key to the Brazilian species-groups and new species is provided. Information on the distribution, depository, and a list of previously described taxa from Brazil are also provided. The species described herein increases the number of Pintalia species described for Brazil to thirty-two, and ninety-four in the Americas in total.